(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Cerebral venous sinus thrombosis (CVST) is an uncommon form of stroke with diverse clinical presentation, predisposing factors, brain imaging findings, and outcome. Objectives: The objective of the study was to evaluate the risk factors associated with cerebral venous sinus thrombosis and hospital outcome of patients treated conservatively with medical management. Methodology: This prospective observational study was conducted in the inpatient department of neurology at national institute of neurosciences and hospital, Dhaka, Bangladesh over a period of 18 months, from June 2017 to December 2018. Total 50 Patients fulfilling the inclusion & exclusion criteria, were included in this study. All the study patients were evaluated clinically and routine laboratory investigation, specific investigation to confirm the diagnosis of venous sinus thrombosis along with special investigation to find out possible risk factors were done. All patients after diagnosis of venous thrombosis medical treatment with LMWH were given. Results: A total of 50 patients of CVST were included with age more than 18 years. Among them 34 (68%) were females and 16 (32%) were males with average age 28.48 ± 9.55 years in both sexes. Out of 50, 48(96%) patients were presented with symptoms of headache, of total 44(88%) had vomiting and 30(42%) had blurring of vision or double vision, 11 (22%) had Seizures, 12(24%) had altered level of consciousness and limb weakness was observed only 10 (20%) patients. Most common risk factors were Oral contraceptive pill (OCP), which was 25 (78.1%) and puerperium 8(23.1%) among females, infections were 11(22%) and no risk factors were found among 11(22%) of study patients overall. Both superficial and deep venous system were involved. Transverse sinus was most commonly involved and was involved 45 (90%) patients. Mean hospital stay was 12.46 days, most of the patient had significant improvement of symptoms and signs during discharge from hospital after treatment, only 4(8%) patients were died. Conclusion: Cerebral venous sinus thrombosis is a uncommon form of stroke, early diagnosis can be made with high degree of clinical suspicion and available neuroimaging, mortality and morbidity can be reduced by early diagnosis and initiation of treatment. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):13-18